Exoplanet detection in rotational shearing interferometry through experimental setup and digital filtering techniques - Montes-Flores, Manuel; Garcia-Torales, Guillermo; Strojnik, Marija (Advanced Optical Technologies, 2025)
The significant brightness contrast between stars and orbiting planets often hinders the detection of exoplanets. This paper presents the development and validation of an experimental setup and digital filtering techniques for a rotational shearing interferometer (RSI) aimed at enhancing exoplanet detection. The method leverages controlled phase shifts and spatial frequency modulation through Risley and Dove prisms to isolate faint planetary signals from dominant starlight. Laboratory experiments use HeNe lasers to simulate a star-planet system, and spatial filters ensure precise wavefront alignment. The interferometer’s rotational shearing capabilities enhance the accuracy of phase alignment, allowing for significant suppression of starlight and improved detection of planetary signals. Additionally, applying Fourier-based digital filtering techniques further enhances detection sensitivity by reducing background noise. Experimental results demonstrate an 80% reduction in noise and up to a 20% increase in detection sensitivity compared to traditional interferometric methods. The RSI’s performance represents a significant advancement in interferometric techniques, suggesting its potential for real-world astronomical applications. However, further optimization is required to address challenges associated with space-based observations. This work sets the foundation for future research aimed at refining optical configurations and digital filtering techniques for exoplanet detection.